Вы находитесь на странице: 1из 7

C 2 1/2 2 L 2 (R) L 2 [0, 1] L 2 (R + )

n f H y ∈ H f (x) = (y, x) x ∈ H

L 2 (R)

ˆ

L = i

∂x ,

L : D( L) → L 2 [0, a],

ˆ

ˆ

ˆ

D( L) = { ψ ∈ L 2 [0, a]

ˆ

L

=

i

∂x ,

L ˆ : D( L) → L 2 [0, a],

ˆ

:

ψ(0) = ψ(a) }.

ˆ

D( L) = { ψ ∈ L 2 [0, a] : ψ(0) = ψ(a), ψ (0) = ψ (a) }

ˆ

H

x = 0 x = a

ˆ

H

µ f (x) = [x], x 0 L 2 (R, dµ)

U : L 2 [0; a]

ψ A

L 2 (M, dµ)

ˆ

ˆ

Aψ = 0

ψ = 1/ a

ψ (x) ∈ L 2 (R) pF [ψ(x)](p) ∈ L 2 (R)

U(x) = 2 æ 0 δ(x).

m

ψ (+0) ψ (0) = 0 ψ(0)

T ˆ a = e ipa/ˆ

T ˆ p a = e ip a x/ˆ

e i Iφ sign I θ ( I )

A = T a + T a λ e i Ht/ ψ(x)

ˆ

ˆ

ˆ

ˆ

ˆ

ˆ

ˆ

i ψ ∂t

=

ˆ

ˆ

ψ(x) D( H)

H = ( 2E

ˆ

E

E

2E

) .

ψ(t) = ( ψ

1

ψ 2 (t) ) .

(t)

t > 0

ψ(t) = (

1 0 )

w(t) = 1 2 + 3 cos 2Et

4

.

t > 0

U 0 2a

x < 0 x < 0 i ∂/∂x U 0 x [0, a]

ˆ

P λ

ˆ

P ω ω R

P λ T a [a, b]

ˆ

ˆ

L 2 (R)⊗L 2 (R) L 2 (R 2 )

xˆ pˆ aˆ + H aˆ H ψ

λ aˆ + ψ λ+ ω

t = 0 ψ(x, 0) =

1

2 ψ k (x) +

1

2 ψ k+1 (x) ψ(x, t) t > 0 ψ k k

t = 0 ψ(x, 0) =

1

2 ψ k (x)

1

2 ψ n (x) ψ(x, t) t > 0 ψ k k

ψ 0 (x) a) n ψ k (x) ψ k (x) k a + ) n ψ 0 (x) ψ 0 (x)

aˆ + ψ n (x) = n + 1ψ n+1 (x)

ψ λ (x) D( H) |n |n ψ(x, t) t = 0 ψ(x, 0) = xe x 2 /2

l = 1

ˆ

e i l z φ 0 ψ(r, θ, φ)

e iσˆ n φ 0 /2 φ 0 = π/2 OY /2 OX /2 φ = 2π OZ /2

|ψ= c 1 |200+ c 2 |210 c 1 c 2 ψ(x, y, z) = c 1 |1⟩|0⟩|0+ c 2 |0⟩|1⟩|0 c 1 c 2

l z φˆ

ˆ